2001
DOI: 10.1097/00022744-200109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: of the breast has attracted attention because of its relatively good prognosis, in spite of its high cytologic grade. It has, by definition, a consistent, florid tumor infiltrating lymphocyte (TIL) population, probably the result of cytotoxic T-lymphocytes recognizing tumor cells in an HLA-DR-restricted manner. HLA-DR tends to be more highly expressed on primary medullary carcinoma cells than on ductal carcinoma cells; however, the MHC-class II antigenicity of the tumor cells themselves has not been analyzed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Furthermore, in breast cancer, the extent of HLA-DR expression appears to be related to tumor grade. In fact, two studies reported that none of the breast carcinomas that were negative or only focally positive for HLA-DR expression were well differentiated (Zuk and Walker, 1988;Brunner et al, 1991); in addition, high levels of HLA-DR antigens expression were detected on primary medullary breast carcinoma which is usually associated with a relatively favorable prognosis (Natali et al, 1983;Bartek et al, 1987;Yazawa et al, 1993;Feinmesser et al, 2000;Lazzaro et al, 2001). In spite of these evidences, a number of studies failed to support a prognostic relevance of HLA-DR antigens in breast cancer (Perez et al, 1986;Wintzer et al, 1990;Lucin et al, 1994).…”
Section: Distribution Of Hla-dr Antigens In Solid Malignanciesmentioning
confidence: 99%
“…Furthermore, in breast cancer, the extent of HLA-DR expression appears to be related to tumor grade. In fact, two studies reported that none of the breast carcinomas that were negative or only focally positive for HLA-DR expression were well differentiated (Zuk and Walker, 1988;Brunner et al, 1991); in addition, high levels of HLA-DR antigens expression were detected on primary medullary breast carcinoma which is usually associated with a relatively favorable prognosis (Natali et al, 1983;Bartek et al, 1987;Yazawa et al, 1993;Feinmesser et al, 2000;Lazzaro et al, 2001). In spite of these evidences, a number of studies failed to support a prognostic relevance of HLA-DR antigens in breast cancer (Perez et al, 1986;Wintzer et al, 1990;Lucin et al, 1994).…”
Section: Distribution Of Hla-dr Antigens In Solid Malignanciesmentioning
confidence: 99%